Strategi Menemukan Jalan Keluar Labirin dengan Waktu Tercepat Menggunakan Metode DFS - Mustika Rahmasuci; Husnul Hotimatus Sahroh; Maulina Azizah; Putri Wulandari; Diah Adistia; Saiful Bukhori (INFORMAL: Informatics Journal, 2017)
Depth-first search algorithm are blind search process and deepen search follow a single track until found goal. Maze is complicated network way and tortuous, also have many deadlock. Maze often become a challenge in a game like puzzle, which one there’s an object in start position have find way out on specify position. in this journal we’ll discuss about utilization DFS on maze and fastest time to find way out.